Induction of Relaxation by Autonomous Sensory Meridian Response - Sakurai, Noriko; Ohno, Ken; Kasai, Satoshi; Nagasaka, Kazuaki; Onishi, Hideaki; Kodama, Naoki (Frontiers in Behavioral Neuroscience, 2021)
Background Autonomous sensory meridian response is used by young people to induce relaxation and sleep and to reduce stress and anxiety; it comprises somatosensation caused by audiovisual stimuli (triggers) that lead to positive emotions. Auditory stimuli play the most important role among the triggers involved in ASMR and have been reported to be more triggering than visual stimuli. On the other hand, classical music is also known to have a relaxing effect. This is the first study to clarify the difference in brain activation associated with relaxation effects between ASMR and classical music by limiting ASMR to auditory stimulation alone. Methods Thirty healthy subjects, all over 20 years of age, underwent fMRI while listening to autonomous sensory meridian response and classical music. We compared the differences in brain activation associated with classical music and ASMR stimulation. After the experiment, the subjects were administered a questionnaire on somatosensation and moods. After the experiment, the participants were asked whether they experienced autonomous sensory meridian response somatosensation or frisson. They were also asked to rate the intensity of two moods during stimulation: “comfortable mood,” and “tingling mood.” Result The results of the questionnaire showed that none of the participants experienced any ASMR somatosensation or frisson. Further, there was no significant difference in the ratings given to comfort mood, but there was a significant difference in those given to tingling mood. In terms of brain function, classical music and ASMR showed significant activation in common areas, while ASMR showed activation in more areas, with the medial prefrontal cortex being the main area of activation during ASMR. Conclusions Both classical music and the ASMR auditory stimulus produced a pleasant and relaxed state, and ASMR involved more complex brain functions than classical music, especially the activation of the medial prefrontal cortex. Although ASMR was limited to auditory stimulation, the effects were similar to those of listening to classical music, suggesting that ASMR stimulation can produce a pleasant state of relaxation even if it is limited to the auditory component, without the somatic sensation of tingling.